2018
DOI: 10.1080/10942912.2018.1522330
|View full text |Cite
|
Sign up to set email alerts
|

Quality predictive models for bovine liver during storage and changes in volatile flavors

Abstract: Protein and fat oxidation are important factors that influence the quality of bovine liver. The objectives of this study were to investigate the degree of oxidation changes in bovine livers during 90d at different temperatures (−20°C, −10°C, 0°C, 10°C, and 20°C), and to develop Arrhenius models to predict its degree of oxidation.Carbonyl, thiobarbituric acid (TBA), peroxide value (POV) as oxidation attributes of bovine liver during storage were measured at different time and the changes were kinetically modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…It has been reported that because the gastrointestinal tract of infants and young children is not fully developed, protein digestibility in the gastrointestinal tract is low, reducing protein availability [22,23]. Moreover, meat products are also susceptible to protein oxidation and lipid oxidation during storage, leading to a decrease in quality and nutritional value [24], which can also affect protein digestibility. There is a lack of adequate reporting on studies of changes in product quality during storage affecting digestibility and digestive characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that because the gastrointestinal tract of infants and young children is not fully developed, protein digestibility in the gastrointestinal tract is low, reducing protein availability [22,23]. Moreover, meat products are also susceptible to protein oxidation and lipid oxidation during storage, leading to a decrease in quality and nutritional value [24], which can also affect protein digestibility. There is a lack of adequate reporting on studies of changes in product quality during storage affecting digestibility and digestive characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic models as well as models based on artificial neural network are the powerful tool for studying the change in food quality indices during the storage period (Kaczmarek et al 2015;Stangierski et al 2019;Limbo et al 2010;Wang et al 2020;Wenjiao et al 2014;Zhang et al 2020;Guo et al 2018;Delgado et al 2016;Panagou et al 2011;Singh 2009). Therefore, the aim of the study was to develop and compare the predictive models of lipid oxidation in minced raw pork meat enriched with selected plant extracts by investigation TBARS values changes during storage at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic models as well as models based on artificial neural networks (ANNs) are a powerful tool for studying the changes in food quality indices during the storage period [21][22][23][24][25][26][27][28][29][30]. Therefore, the aim of the study was to develop predictive models of protein oxidation, expressed in thiol (SH) group decrease in minced raw and heat-treated chicken meat enriched with selected plant extracts during storage at different temperatures.…”
Section: Introductionmentioning
confidence: 99%